The Juridical Contribution of the Federal Sharīʿat Court (Fsc) In the Islamization of Laws in Pakistan: A Study of Leading Cases - Afrasiab Ahmed Rana; Dr. Syed Muhammad Shahid Tirmazi; Dr. Kulsoom Fatima; Dr. Muhammad Amin Ud Din; Dr. Imtiaz Ahmad (Correspondence Author); Fiza Zulfiqar (Al-Qanṭara, 2023)
Islamization means making the laws in conformity with Islam, amending the existing laws in Pakistan and striking down the laws not in conformity with Islamic Law and Shariah. The constitution has enacted special provision for Islamization of Islam, especially Article 227 requires that laws in Pakistan shall be enacted and made in conformity with Islam. Federal Shariat Court (FSC) was made with the aim to protect and to promote the Islamization of laws in Pakistan. From the petition calling into the question Islamic status of the Law reforms Act, 1972 in 1979 till the petition challenging the vires of the Transgender Persons (Protection of Rights) Act, 2018 in 2020, FSC has played a crucial role in upholding Islamization of the Law in Pakistan. This paper will provide a case law analysis of 8 less popular leading judgments in order to elaborate the role of FSC in Islamization of Laws in Pakistan.